Mesenchymal Stem/Stromal Cells in Liver Fibrosis: Recent Findings, Old/New Caveats and Future Perspectives - Fiore, Esteban Juan (2015)
Mesenchymal stem/stromal cells (MSCs) are progenitors which share plastic-adherence capacity and cell surface markers but have different properties according to their cell and tissue sources and to culture conditions applied. Many recent publications suggest that MSCs can differentiate into hepatic-like cells, which can be a consequence of either a positive selection of rare in vivo pluripotent cells or of the original plasticity of some cells contributing toMSC cultures. Apossible role of MSCs in hereditary transmission of obesity and/or diabetes as well as properties of MSCs regarding immunomodulation, cell fusion and exosome release capacities are discussed according to recent literature. Limitations in methods used to track MSCs in vivo especially in the context of liver cirrhosis are addressed as well as strategies explored to enhance their migratory, survival and proliferation properties, which are known to be relevant for their future clinical use. Current knowledge regarding mechanisms involved in liver cirrhosis ameliorationmediated by naïve and genetically modified MSCs as well as the effects of applying preconditioning and combined strategies to improve their therapeutic effects are evaluated. Finally, first reports of GMP guidelines and biosafety issues in MSCs applications are discussed.